2011
DOI: 10.1095/biolreprod.110.090621
|View full text |Cite
|
Sign up to set email alerts
|

Sertoli Cell-Specific Deletion of the Androgen Receptor Compromises Testicular Immune Privilege in Mice1

Abstract: In the mammalian testis, meiotic and postmeiotic germ cell antigens are granted immune privilege. Both local immune suppression and specialized intercellular junctions between somatic Sertoli cells have been proposed to contribute to a highly restricted and effective blood-testis barrier (BTB) that helps maintain tolerance to germ cell antigens. Several studies have suggested that androgens play a role in immune suppression, although direct evidence for this is lacking. We previously reported that Sertoli cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 40 publications
2
61
0
Order By: Relevance
“…It is noted that the intratesticular testosterone level, such as in the seminiferous tubule fluid, is maintained at ϳ100 times the level found in the systemic circulation in both humans and rodents (10 Ϫ7 versus 10 Ϫ9 M) (Turner et al, 1984;Jarow and Zirkin, 2005) to sustain spermatogenesis. Earlier findings coupled with studies using transgenic mouse models have demonstrated that androgens are crucial in the regulation of almost every aspect of spermatogenesis, including spermatogonial proliferation and differentiation, germ cell cycle progression through meiosis, spermiogenesis, spermiation, and cell adhesion at the Sertoli-Sertoli and Sertoli-germ cell interface in the seminiferous epithelium Ruwanpura et al, 2010;Verhoeven et al, 2010;O'Donnell et al, 2011) and to confer immune privilege in the testis (Meng et al, 2011). These effects are mediated via androgen receptor (AR) using genomic and/or nongenomic pathways (Walker, 2009(Walker, , 2010Lamont and Tindall, 2010;Shupe et al, 2011).…”
Section: Tight Junction (Zonula Occludens) and Basal Ectoplasmic Specmentioning
confidence: 99%
“…It is noted that the intratesticular testosterone level, such as in the seminiferous tubule fluid, is maintained at ϳ100 times the level found in the systemic circulation in both humans and rodents (10 Ϫ7 versus 10 Ϫ9 M) (Turner et al, 1984;Jarow and Zirkin, 2005) to sustain spermatogenesis. Earlier findings coupled with studies using transgenic mouse models have demonstrated that androgens are crucial in the regulation of almost every aspect of spermatogenesis, including spermatogonial proliferation and differentiation, germ cell cycle progression through meiosis, spermiogenesis, spermiation, and cell adhesion at the Sertoli-Sertoli and Sertoli-germ cell interface in the seminiferous epithelium Ruwanpura et al, 2010;Verhoeven et al, 2010;O'Donnell et al, 2011) and to confer immune privilege in the testis (Meng et al, 2011). These effects are mediated via androgen receptor (AR) using genomic and/or nongenomic pathways (Walker, 2009(Walker, , 2010Lamont and Tindall, 2010;Shupe et al, 2011).…”
Section: Tight Junction (Zonula Occludens) and Basal Ectoplasmic Specmentioning
confidence: 99%
“…61 Androgens also regulate the testicular immunoprivileged status. [64][65][66] Notably, androgens would not directly affect testicular immune cells because these cells lack the androgen receptor.…”
Section: Immune Privilege In the Testismentioning
confidence: 99%
“…Conditional knockout of the androgen receptor in SCs in mice impairs testicular immune privilege, possibly due to the impairment of BTB permeability. 65,71 Taken together, androgens would contribute to testicular immune privilege by negatively regulating the local immune responses and systemic tolerance to auto-antigens.…”
Section: Immune Privilege In the Testismentioning
confidence: 99%
“…An example of the immunological importance of the BTB/SC barrier in spermatogenesis was demonstrated in SC specific androgen receptor knock out mice (Ar-KO) [33]. In these mice, biotin was detected in the adluminal compartment indicating increased permeability of the BTB/SC barrier to small molecules.…”
Section: Blood-testis-barrier/sertoli Cell Barrier and Its Role Inmentioning
confidence: 99%